Thermal mapping and determination of monitoring points in drug storage (Research, Society and Development, 2022)
In order to retain medicine's quality levels up, it's necessary to store it according to the temperature and humidity specifications determined by the manufacturer, from its manufacturing date to its application on patients. Storages that hold these types of products make use of measuring instruments (thermohygrometers) that track temperature and humidity parameters on a daily basis. The objective of this study was to determine the quantity and location of monitoring points in a new storage, for this, initially a thermal qualification study was carried out, in order to verify the thermal distribution and identify the points that should be monitored. In this study, a thermal qualification was performed during a period of 168 (one hundred and sixty-eight) hours. Based on the results along with a general assessment of the storage, methodologies were established to determine optimal points for monitoring. According to the dimensions between each monitoring point in the area, it was concluded that 24 instruments were needed with an addition of 9 instruments to cover critical points for proper thermal qualification, for a total of 33 instruments to accurately monitor the temperature and humidity within the storage.